Narzędzia web 2.0 w codziennej pracy nauczyciela języków obcych - Górska, Weronika (Neofilolog, 2019)
This article presents the possibility of using online resources with special regard to web 2.0. Using the example of given project carried out in the language school on students taking part in a one-year (120h) language course, the author shows how New Technologies can be used for the development of the students’ skills. In conclusion the author presents some implications of the project, worth considering by teachers. “Technologia sama w sobie nie zmieni edukacji, liczy, się to jak jest użyta.” J. Haymore Sandholtz, C. Ringstaff, D. C. Dwyer Teachers College Press (1997: 10)